The nine kittens of Christmas [videorecording (DVD)] - Dobson, Erinne, 1976-; Routh, Brandon; Sustad, Kimberley; Harrison, Gregory, 1950-; Bennett, Stephanie; Roberts, Sheila, 1951- (Hallmark Channel ; Cinedigm, 2022)
Cat lovers Zachary and Marilee are thrown back together at Christmas when they're tasked with finding homes for a litter of adorable kittens.